Bang the Can Slowly: An Investigation into the 2017 Houston Astros. Issue 2 (3rd April 2022) - Elmore, Ryan; Matthews, Gregory J.
Abstract: This article is a statistical investigation into the 2017 Major League Baseball scandal involving the Houston Astros, the World Series championship winner that the same year. The Astros were alleged to have stolen their opponents' pitching signs in order to provide their batters with a potentially unfair advantage. This work finds compelling evidence that the Astros on-field performance was significantly affected by their sign-stealing ploy and quantifies the effects. The three main findings in the article are (i) the Astros' odds of swinging at a pitch were reduced by approximately 27% (OR: 0.725, 95% CI: (0.618, 0.850)) when the sign was stolen, (ii) when an Astros player swung, the odds of making contact with the ball increased roughly 80% (OR: 1.805, 95% CI: (1.342, 2.675)) on non-fastball pitches, and (iii) when the Astros made contact with a ball on a pitch in which the sign was known, the ball's exit velocity (launch speed) increased on average by 2.386 (95% CI: (0.334, 4.451)) miles per hour.